(3MGTjI GdNWjH CHh GdaVd Ydi TQM LdGd GdOjf GdOhGfj dehGba GdEjLjs - (3GdNWjH CHh GdaVds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf bhdg HYK Gddg Edi GdNdb M ajg Cf GdVejQ Edi GdfHj GdePchQ hdG jNai Cfg SjOfG hfHjfG eMeO NGJe GdfHjjfs
(3BNQgG (B:s
(3bhdg GdbOQI GdeDKQI aj GdWGYI M ajg Cf GdTjN GdCTYQj dG jbhds
(3aj Chdg fbhds
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdadSaI hGdefWbs